Review of Goniozus Förster, 1856 (Hymenoptera: Bethylidae) of Korea, with descriptions of two new species - Lim, Jongok; Lee, Seunghwan (Zootaxa, 2012)
Five species of Goniozus are recognized in Korea. Goniozus koreanus Lim, sp. nov. and G. mesolevis Lim, sp. nov. are described and figured; G. akitsushimanus Terayama, 2006 and G. yoshikawai Terayama, 2006 are newly recorded from Korea. Goniozus maurus Marshall, 1905 is excluded from Korean fauna. A key to the Korean species in females is provided.